SCN1-1 RELEATED DISORDERS: DRAVET SYNDROME (International Educators Conference, 2025)
SCN1A-Related Disorders - the most common epilepsies exacerbated by fever are caused by pathogenic variants in the SCN1A gene, which lead to various syndromes, including Dravet syndrome (DS) and genetic epilepsy with febrile seizures plus (GEFS+). DS in particular is highly associated with loss-of-function SCN1A mutations; GEFS+ is more heterogeneous and is associated with multiple other genetic variants as well as some SCN1A gain-of-function mutations.